Effect of dietary supplementation with aspirin eugenol ester on performance and ileum health in broilers under high stocking density stress conditions - Ma, Penghui; Zhang, Yi; Bai, Dongying; Zhen, Wenrui; Guo, Caifang; Ito, Koichi; Zhang, Bingkun; Ma, Yanbo (Frontiers in Veterinary Science, 2025)
This study investigated the influence of dietary aspirin eugenol ester (AEE) on growth performance, ileum antioxidant capacity, intestinal barrier function and ileum microbiota of broilers subjected to high stocking density stress (HDS). A total of 360 one-day-old Arbor Acres broilers were randomly assigned to four treatment groups: normal density (ND, 14 broilers/m2), normal density + AEE (NDAEE), high density (HD, 22 broilers/m2) and high density + AEE (HDAEE). HDS leads to a significant decrease in broiler performance while reducing the antioxidant capacity of the gut. Morphologic examination of the intestine revealed that HDS causes damage to the intestinal villi. Dietary addition of AEE significantly increased body weight gain and improved antioxidant capacity with restoration of intestinal morphology in broilers with HDS. In addition, HDS resulted in decreased gene expression of ileum tight junction proteins and significantly increased gene expression of inflammatory factors in broilers. Dietary addition of AEE effectively alleviated the decrease in tight junction protein gene expression in broilers with HDS and reduced the expression of HDS-induced inflammatory cytokines through the COX-2-mPGES-1 signaling pathway. AEE supplementation improved microbiota diversity and increased the relative abundance of Lactobacillus and Ileibacterium. Thus, dietary AEE effectively reduced the negative effects of HDS on productivity, gut microbiota and overall health in broilers and could be a worthwhile dietary supplement for offsetting negative effects of stocking stress in broilers.